1998
DOI: 10.1111/j.1151-2916.1998.tb02353.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Mechanical Properties of Pressureless‐Sintered Niobium‐Alumina‐Matrix Composites

Abstract: Niobium-alumina (Nb-Al 2 O 3 ) composites have been fabricated via the pressureless sintering of compacts of intensively milled Nb-Al 2 O 3 mixtures. Strength and fracture toughness of the composites increase as the niobium content increases. For a composite that contains 50 vol% niobium, strengths of up to 680 MPa, with a corresponding fracture toughness of 6.3 ± 0.3 MPaؒm 1/2 and hardness of 6.4 GPa, have been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Further details of the processing technique are reported elsewhere. 4,14 The densities of composite C1 and C0 were ϳ98% and ϳ95% of the theoretical density, respectively (Table I) …”
Section: (1) Processingmentioning
confidence: 99%
“…Further details of the processing technique are reported elsewhere. 4,14 The densities of composite C1 and C0 were ϳ98% and ϳ95% of the theoretical density, respectively (Table I) …”
Section: (1) Processingmentioning
confidence: 99%
“…Often, the ceramic phase has a significantly different thermal expansion coefficient than the metal phase, resulting in the development of stresses during thermal cycling. The Al 2 O 3 –Nb system is interesting because of the near match in the coefficient between the ceramic and metal phases 69,70 . Presumably, the thermal expansion match should minimize the residual stresses and allow for improved performance in applications requiring thermal cycling, if the interfacial adhesion is sufficient.…”
Section: Case Studiesmentioning
confidence: 99%
“…The Al 2 O 3 -Nb system is interesting because of the near match in the coefficient between the ceramic and metal phases. 69,70 Presumably, the thermal expansion match should minimize the residual stresses and allow for improved performance in applications requiring thermal cycling, if the interfacial adhesion is sufficient. Alumina-Nb composites can be formed by RHP using the following reaction: 71 10 Al þ 3…”
Section: The Al 2 O 3 -Nb Systemmentioning
confidence: 99%
“…It was found that reaction sintering can also be used to manufacture highly dense Fe/Al 2 O 3 , Cr/Al 2 O 3 , or Nb/Al 2 O 3 cermets. 4,[7][8][9] These intermetallic or metal-reinforced alumina composites exhibit several advantages compared to single-phase ceramic materials, such as high strength, good wear resistance, improved fracture toughness, and tailorable electrical properties. The precursor powder mixtures for 3A-materials contain metal oxides (e.g., ZrO 2 , Fe 2 O 3 , TiO 2 , Nb 2 O 5 ), Al, and Al 2 O 3 or elemental metals (e.g., Fe, Nb), Al, and Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%